Disentangling minimum clinically important difference for an individual and a population in the treatment of Alzheimer's disease - Changyu Shen; Robert W. Platt; Shibeshih Belachew; Hiroko H. Dodge (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2025)
Abstract Recent accelerated and traditional approval of anti‐amyloid therapies by the U.S. Food and Drug Administration for the treatment of patients with early Alzheimer's disease has stimulated heated debate on whether or not the benefits of these therapeutic agents achieve a minimum clinically important effect size, or minimum clinically important difference. We argue that these debates are rooted in the entanglement of two fundamentally different concepts, the minimum clinically important difference for an individual versus that of a population. At the core of the indiscrimination between the two concepts is the unrealistic requirement or expectation that a drug should provide the same clinically important effect for every patient in the target population to be considered achieving meaningful benefit for the population. We discuss the difference and connection between the two concepts to facilitate the communication about their difference and relatedness. Highlights Minimum clinically important difference (MCID) is defined for an individual and population‐level mimimum clinically important difference (pMCID) is defined for a population. MCID and pMCID are fundamentally different measures. We established their connection and showed in general pMCID < MCID. Discussion of effect size of Alzheimer's disease treatments should clearly distinguish the two measures.